Can Reforms Promoting Growth Increase Financial Fragility? An Empirical Assessment - Caldera Sánchez, Aida (OECD Economics Department Working Papers, 2016)
Certain growth-promoting policies can have negative side-effects by increasing the vulnerability of economies to financial crises. Typical examples are greater openness to financial flows or more liberalised financial markets. This paper investigates whether the growth benefits of policy reforms in these growth-enhancing areas, and others such as trade openness, exceed the possible costs of occasional, albeit potentially severe, crises for a sample of 100 developed and emerging economies from 1970 to 2010. The results suggest that the pro-growth effects of greater capital account openness outweigh the negative effects of a higher propensity to twin crises. Greater domestic financial liberalisation is associated with faster growth, but also with a higher propensity to systemic banking and twin crises. A free floating exchange rate and greater openness to trade, by reducing the likelihood of currency crises, are associated with higher growth. While pro-competitive product market regulations and lower corporate taxes are associated with higher growth, they do not seem to influence financial fragility via higher probability of crises